Effect of hyperhomocysteinemia on the prognostic value of triglyceride glucose index in patients with acute coronary syndrome - Kan, Yi; Ma, Xiaoteng; Zhao, Zehao; Dong, Shutong; Xu, Yinxiao; Sun, Yan; Cheng, Yujing; Zhang, Dai; Liu, Yuyang; Liu, Xiaoli; Shi, Dongmei; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe prognostic value of triglyceride-glucose (TyG) has been well described in patients with coronary artery disease (CAD). Hyperhomocysteinemia (HHcy) promotes insulin resistance and has also been regarded as a potential risk factor for cardiovascular disease. However, the prognostic value of TyG in acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) and the interaction between TyG and HHcy remain unclear.MethodsA total of 1,734 ACS patients undergoing PCI were continuously enrolled between June 2016 and November 2017 at Beijing Anzhen Hospital. Patients were categorized into four groups based on HHcy status and the optimal cut-off value of TyG. The primary endpoint was major adverse cardiovascular events (MACE), a composite of all-cause death, nonfatal myocardial infarction, nonfatal stroke, and unplanned repeat revascularization.ResultsOver a median follow-up of 927 days, 358 patients (20.6%) experienced MACE. The Kaplan-Meier curves showed significant differences in the cumulative incidence of MACE among prespecified groups (p < 0.001). Multivariable Cox regression analysis revealed that higher TyG was significantly associated with an increased risk of MACE in patients without HHcy (HR: 2.36, 95% CI: 1.53–3.64, p < 0.001), but not in patients with HHcy (HR: 1.31, 95% CI: 0.60–2.87, p = 0.503). Restricted cubic splines only demonstrated the prognostic value of TyG in patients without HHcy. A significant interaction was observed for MACE between TyG and HHcy (p for interaction = 0.01).ConclusionsThe prognostic value of TyG was modified by HHcy in ACS patients undergoing PCI. Higher TyG was only associated with an increased risk of MACE in ACS patients without HHcy, but not in ACS patients with HHcy.